Reduction for Compositional Verification of Multi-Threaded Programs - Popeea, Corneliu; Wilhelm, Andreas; Rybalchenko, Andrey (Formal Methods in Computer-Aided Design (FMCAD), 2014)
Automated verification of multi-threaded programs requires keeping track of a very large number of possible interactions between the program threads. Different reasoning methods have been proposed that alleviate the explicit enumeration of all thread interleavings, e.g., Lipton’s theory of reduction or Owicki-Gries method for compositional reasoning, however their synergistic interplay has not yet been fully explored. In this paper we explore the applicability of the theory of reduction for pruning of equivalent interleavings for the automated verification of multi-threaded programs with infinite-state spaces. We propose proof rules for safety and termination of multi-threaded programs that integrate into an Owicki-Gries based compositional verifier. The verification conditions of our method are Horn clauses, thus facilitating automation by using off-the-shelf Horn clause solvers. We present preliminary experimental results that show the advantages of our approach when compared to state-of-theart verifiers of C programs.